THE EXPERIENCE OF LEAVING THE OCCUPIED KHERSON THROUGH THE PRISM OF ORAL HISTORY (Південний архів (історичні науки), 2024)
The purpose of the research is to reconstruct the experience of the residents’ leaving Kherson occupied by Russian military forces and to identify the main motivation for Kherson dwellers’ leaving the city during different stages of occupation on the basis of the analysis of oral history materials. The methodological fundamentals of the research are oral and local history which allows presenting the chosen topic most thoroughly and comprehensively. The main research results. The Russian-Ukrainian war has already been called the most documented war. However, it is impossible to reconstruct many pages of the Ukrainian resistance using usual documentary sources, photos or video materials. Many events of the life in the occupied city, especially the circumstances of leaving the occupied city, cannot be reconstructed from such sources because they are not available. It is possible to imagine the difficulties arising on the road to the territory controlled by Ukraine in the period from March 1 to November 11, only using oral-historical evidences of the people who underwent this ordeal. Leaving the occupied city involved massive multiple inspections of all gadgets at the Russian checkpoint, consequently, it was impossible to take photos or videos. Therefore, the main source of our research is documented stories of Kherson residents. The respondents were the city dwellers of different age, professions, marital statuses and incomes. Their psychological readiness to share their experience of leaving the occupied city allows reconstructing events unfolding on the roads of Kherson region. Moreover, due to these stories, we are able to reveal the depth of the people’s emotional experiences, the traumatic nature of the events affecting them both physically and psychologically. This is a basis not only for reconstructing facts of the modern war, but also for filling the history with moral-psychological content. Our research reveals the following key aspects: the psychological state of the inhabitants of the occupied territories; readiness/unreadiness to organize their life space in the restricted conditions of the occupation; motivation for leaving; prevalence of the fear of staying in the occupied territory over the fear of all circumstances of leaving; the danger the people faced on the road to the territory controlled by Ukraine; the occupiers’ behavior towards the civilian population. Conclusions. The interviews allow identifying a number of characteristic aspects of leaving the occupied Kherson: the majority of population did not believe in the possibility of the beginning of a full-scale invasion and were not psychologically ready for the war; different factors affected their decision to leave the (news about the occupiers’ movement across the territory of Ukraine, personal or family needs; the fear of living in the occupied city). The experience of leaving depended on many objective and subjective factors: the period and the accessible route for leaving, the number of checkpoints and the intensity of inspections, psychological readiness/ability to answer the questions asked by the occupiers.
Keywords: Kherson, war, full-scale invasion, occupation, experience of leaving